2015
DOI: 10.1155/2015/651757
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Factors Related to the Secretion of Glucagon-Like Peptide-1

Abstract: The glucagon-like peptide-1 is secreted by intestinal L cells in response to nutrient ingestion. It regulates the secretion and sensitivity of insulin while suppressing glucagon secretion and decreasing postprandial glucose levels. It also improves beta-cell proliferation and prevents beta-cell apoptosis induced by cytotoxic agents. Additionally, glucagon-like peptide-1 delays gastric emptying and suppresses appetite. The impaired secretion of glucagon-like peptide-1 has negative influence on diabetes, hyperli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 114 publications
1
31
0
7
Order By: Relevance
“…A previous study conducted on the same group of chickens showed that in ovo treatment with synbiotics caused lower total lipid content in breast muscles of 42-day-old chickens; however, this effect was significant in the case of S2 injection [15]. Moreover, SCFAs are also implicated in the regulation of blood glucose levels by increasing insulin secretion and decreasing the production of glucagon in response to SCFA-induced GLP-1 secretion [31,34]. The results of the current study revealed a trend toward lower plasma glucose and higher insulin levels on day 7 in birds from both experimental groups; however, these values did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study conducted on the same group of chickens showed that in ovo treatment with synbiotics caused lower total lipid content in breast muscles of 42-day-old chickens; however, this effect was significant in the case of S2 injection [15]. Moreover, SCFAs are also implicated in the regulation of blood glucose levels by increasing insulin secretion and decreasing the production of glucagon in response to SCFA-induced GLP-1 secretion [31,34]. The results of the current study revealed a trend toward lower plasma glucose and higher insulin levels on day 7 in birds from both experimental groups; however, these values did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 98%
“…The incretin hormone, GLP-1 released from the enteroendocrine L-cells of the intestine, stimulates the release of insulin from β-cells through distinct G-protein-coupled receptors highly expressed on the cells (Mignone, Wu, Horowitz, & Rayner, 2015). GLP-1 is rapidly degraded by DPP-IV, an ubiquitous enzyme expressed on the surface of most cell types (Green, Gault, O'Harte, & Flatt, 2004 (Wang, Liu, Chen, Li, & Qu, 2015).…”
Section: Effect Of Salmon-derived Hydrolysates On Glp-1 Release From mentioning
confidence: 99%
“…TGR5 локалізується на клітинах нейронів міжм'язового сплетення кишечника, L-клітинах кишечника, печінки й спинного мозку. За допомогою L-клітин УДХК стимулює секрецію глюкагоноподібного пептиду-1 (glucagon-like peptide-1, GLP-1) і нормалізує секрецію інсуліну [20,21].…”
Section: ключові слова: ожиріння; гастроезофагеальна рефлюксна хворобunclassified